Technical valorisation of spent coffee grounds and food waste using sulphuric acid immobilised on silica. Issue 2 (17th February 2020) - Karmee, Sanjib Kumar
ABSTRACT: Biodiesel from spent coffee grounds and food waste was prepared using sulphuric acid immobilised on silica gel (H2 SO4 –SiO2 ) as a catalyst. Reactions were carried out under reflux conditions using 15 mmol methanol. Food waste lipid and spent coffee oil gave 97% and 92% of biodiesel, respectively, after 24 h of reaction. After completion of the reaction, the immobilised acidic catalyst was separated by gravity filtration. Subsequently, the catalyst was reused for three consecutive cycles. At the end of three cycles, a 22% decrease in catalytic activity was observed for reactions involving spent coffee oil, whereas a 13% decrease in activity was observed during the use of food waste lipid as a starting material.